The Influence of Digital Leadership and Job Crafting on Work Engagement Job Satisfaction as a Mediator Among Millennial and Generation Z Employees - Muhammad Amien Rais Rofik; Osly Usman (Journal of Digital Business and Global Economy, 2026)
The engagement of millennial and Gen Z employees is among the most important issues of modern organizations. This research investigates the role of digital leadership and job crafting in work engagement, with work satisfaction as a mediating variable. The data of 106 professionals was analyzed applying PLS-SEM. The results of the statistical analysis contradict expectations, because it seems that neither digital leadership nor individual job crafting directly influence engagement. Instead, job satisfaction serves as a complete bridging mechanism for both relationships. For the younger workforce, tech-competent management and the freedom to modify tasks are perceived merely as baseline job requirements rather than actual incentives. These factors would create the early workplace satisfaction before they can generate greater professional commitment. This paper contributes to the knowledge of human resources by showing that the happiness of employees is a key condition for the transformation of digital resources into tangible commitment. In other words, the investments in technology are not profitable unless organizations focus on the well-being of internal staff.